2017
DOI: 10.1111/jne.12476
|View full text |Cite
|
Sign up to set email alerts
|

Acyl ghrelin improves cognition, synaptic plasticity deficits and neuroinflammation following amyloid β (Aβ1‐40) administration in mice

Abstract: Ghrelin is a metabolic hormone that has neuroprotective actions in a number of neurological conditions, including Parkinson's disease (PD), stroke and traumatic brain injury. Acyl ghrelin treatment in vivo and in vitro also shows protective capacity in Alzheimer's disease (AD). In the present study, we used ghrelin knockout (KO) and their wild-type littermates to test whether or not endogenous ghrelin is protective in a mouse model of AD, in which human amyloid β peptide 1-40 (Aβ ) was injected into the latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 67 publications
0
28
1
Order By: Relevance
“…More specifically, acylghrelin increased cAMP response element binding protein (CREB) expression and led to the activation of the extracellular signal-regulated kinase 1/2 (ERK1/2) pathway and the promotion of brain derived neurotrophic factor (BDNF) expression in the hippocampus. Moreover, acylghrelin treatment of intrahippocampal amyloid-β injected mice, that mimic aspects of AD, rescued memory deficits 63,64 , decreased neuroinflammation 64 and prevented the amyloid-β induced suppression of hippocampal LTP 64 . Similarly, in amyloid-β injected rats treated with acyl-ghrelin there was a reduction in amyloid-β plaque deposition and attenuation of memory impairments due to increased AMP-activated protein kinase (AMPK) and glycogen synthase kinase (GSK) phosphorylation, and decreased tau phosphorylation 65 .…”
Section: Ghrelin Mediated Hippocampal Memorymentioning
confidence: 95%
“…More specifically, acylghrelin increased cAMP response element binding protein (CREB) expression and led to the activation of the extracellular signal-regulated kinase 1/2 (ERK1/2) pathway and the promotion of brain derived neurotrophic factor (BDNF) expression in the hippocampus. Moreover, acylghrelin treatment of intrahippocampal amyloid-β injected mice, that mimic aspects of AD, rescued memory deficits 63,64 , decreased neuroinflammation 64 and prevented the amyloid-β induced suppression of hippocampal LTP 64 . Similarly, in amyloid-β injected rats treated with acyl-ghrelin there was a reduction in amyloid-β plaque deposition and attenuation of memory impairments due to increased AMP-activated protein kinase (AMPK) and glycogen synthase kinase (GSK) phosphorylation, and decreased tau phosphorylation 65 .…”
Section: Ghrelin Mediated Hippocampal Memorymentioning
confidence: 95%
“…Central application of acylated ghrelin prevents Aβ-induced impairments of memory and energy and glucose metabolisms, probably through increase of AMPK and GSK phosphorylation and decrease of tau phosphorylation (Kang et al, 2015). Further study revealed that acylated ghrelin also blunts Aβ-induced depression of long-term potentiation (LTP) in hippocampus and therefore prevents impairments of recognition and spatial orientation (Santos et al, 2017). Ghrelin ameliorates neurogenesis impairment in hippocampus and improves memory deficits by prevention of synaptic degeneration including cholinergic fiber loss (Moon et al, 2011, 2014).…”
Section: Ghrelin and Alzheimer's Diseasementioning
confidence: 99%
“…In previous studies, different groups have validated the beneficial effects of GHSR1α ligands, including ghrelin and acyl ghrelin, as well as GHSR1α agonists, including MK0677 and LY444711, on hippocampal neurogenesis, long-term potentiation, and cognition against Aβ toxicity in rodent models [14,16,18,55]. Although we have observed impaired neurogenesis in the dentate gyrus in 5xFAD mice and the neurogenic effect of MK0677 treatment, which is in agreement with a previous study [14], our results do not support the protective effect of GHSR1α activation against the development of Aβ-induced synaptic deficits or cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Such discrepancies between previous studies and ours may arise from the use of different types of experimental systems. Two of the aforementioned studies employed Aβ 40 -or Aβ 42 -injected mouse or rat models [18,55]. The acute Aβ toxicity model may not represent the complexity of neuronal changes in response to chronic Aβ production and accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation